Marking and identification methodologies for mass releases of sterile Queensland fruit fly Bactrocera tryoni (Diptera: Tephritidae) an overview. (April 2023) - Dominiak, Bernard C.; Taylor, Phillip W.; Rempoulakis, Polychronis
Abstract: The Sterile Insect Technique (SIT) is a most promising methodology for effective control of the Queensland fruit fly (Qfly), Bactrocera tryoni, a major horticultural pest of Australia . The Qfly SIT has a long history, with a significant amount of research invested, and numerous releases of sterile insects, mainly in NSW and Victoria. In SIT operations worldwide, a reliable insect marking technique is a prerequisite for the successful discrimination among wild and laboratory reared flies in the field, allowing for estimation of wild populations and effective over flooding ratios. For quarantine purposes, often the same requirements apply for declared pest free areas following successful SIT releases programs. A great amount of variation in fluorescent dye performance and visibility has been recorded from several Qfly SIT release projects in the past. Here, we review the past experience from those operations, and the current and developing methods for the marking and identification of Qfly that were mass reared and irradiated for sterile releases. We highlight problems arising from less successful use of fluorescent dyes, and we present novel methodologies that have the potential to substitute the dye in future operations.